Chatting with nature: exploring local plants using AI & Lens - Wan Hanafi, Wan Nurhayati; Mohd Hassan, Wan Rozianoor; Azmir, Izzati Adilah (2025)
This innovation project aims to improve students’ understanding of plant biodiversity through a handson, technology-integrated learning experience. It seeks to foster curiosity, environmental awareness, and digital literacy by combining outdoor exploration with Artificial Intelligence (AI) tools accessed via mobile devices, such as Google Lens and ChatGPT. Students used their mobile devices to photograph local plants, identify them instantly with AI-powered Google Lens, and gather additional insights through ChatGPT. They compiled their discoveries, including plant names, locations, and interesting facts on a collaborative Padlet board, creating a digital plant gallery. Feedback was collected using reflection prompts and rating scales. The activity demonstrated high levels of student engagement, enjoyment, and active participation. Students reported enhanced awareness and understanding of plant diversity and classification. The integration of mobile-based AI tools like Google Lens and ChatGPT deepened learning and made the experience more interactive. The project also encouraged outdoor exploration and fostered meaningful interdisciplinary connections. The project successfully enhanced students’ understanding of plant biodiversity through an engaging, hands-on learning experience. Its flexible design supports diverse educational settings and fosters essential 21st-century skills.